Efficiency, profitability and productivity: Technological applications in the agricultural sector - Pérez-Pons, María Eugenia; Parra-Domínguez, Javier; Chamoso, Pablo; Plaza, Marta; Alonso , Ricardo (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2020)
New technological advances have made it possible to improve precision and efficiency in the consumption of natural resources. This article presents a series of different use cases in which technology has benefited peripheral and cross-border areas and continues to do so. Real-scenario implementations of cutting-edge Internet of Things (IoT) technologies have been conducted in Northern Portugal and Castilla y León. The findings demonstrate the direct impact of technological applications on the regions and the production efficiency.